Retrospective Analysis of Factors Associated With a Revised Fall Prevention Bundle in Hospitalized Patients. (November 2020) - Scheidenhelm, Sandra; Astroth, Kim Schafer; DeLong, Karen; Starkey, Cyndy; Wolfe, David
Abstract : OBJECTIVE: The study aims to describe factors associated and injuries sustained with inpatients who fell while hospitalized and identify the impact of a revised fall-prevention bundle. BACKGROUND: Approximately 1 million falls occur in hospitals annually, accounting for approximately 70% of inpatient accidents. Inpatient falls can result in physical injury, increased patient mortality and morbidity, decreased quality of life, and increased length of stay and cost. METHODS: We used a retrospective review of patient fall data for adult inpatients who fell while hospitalized. RESULTS: After reeducation and implementation of all elements of a revised fall-prevention bundle, there were fewer falls per patient day. We identified additional characteristics indicating when patients were more likely to be injured in a fall. CONCLUSIONS: A fall-prevention bundle is effective in decreasing inpatient falls and falls with injury. Raising awareness of additional factors may decrease risk of injuries during an inpatient fall. Abstract : Supplemental digital content is available in the text.